Estimates of National Output, Distributed Income, Consumer Spending, Saving, and Capital Formation - Hoffenberg, Marvin; Lewis, Mabel S.; Pierson, John H. G. (The Review of Economics and Statistics, 1943)
Marvin Hoffenberg, Mabel S. Lewis, John H. G. Pierson, Estimates of National Output, Distributed Income, Consumer Spending, Saving, and Capital Formation, The Review of Economics and Statistics, Vol. 25, No. 2 (May, 1943), pp. 101-174